Analisis Deskriptif Kualifikasi Guru PJOK pada Kualitas Aktivitas Jasmani di Wilayah 3T dalam Konteks Pencapaian SDG 3 (Good Health and Well-Being) dan SDG 4 (Quality Education) - Febriana Pratiwi (Jurnal Keolahragaan, 2025)
Physical Education, Sports, and Health (PJOK) at elementary schools in Morotai Utara District plays a strategic role in advancing Good Health and Well-being (SDG 3) and Quality Education (SDG 4). This study aimed to describe the availability of qualified PJOK teachers, the implementation of physical activities, and their impact on students’ motor skills and learning motivation. A descriptive mixed-methods survey design involved 10 schools and 30 informants (principals, teachers, and students). Questionnaires, semi-structured interviews, and participatory observations were employed; quantitative data were analyzed using SPSS 24 and qualitative data underwent thematic analysis. Findings revealed that only 20 % of schools employed certified PJOK teachers, PJOK was scheduled once a week, 86.7 % of students perceived activities as unstructured, and 90 % of informants reported declines in motor skills, motivation, and concentration. The study recommends deploying professional PJOK teachers, conducting competency-based training, increasing activity frequency, and investing in infrastructure to enhance PJOK’s contribution to sustainable development.